Serum uric acid: creatinine ratio (UCR) is associated with recurrence of atrial fibrillation after catheter ablation - Zhang, Yujiao; Wang, Yanxin; Yang, Xuesong; Li, Zhan; Shang, Luxiang; Hou, Yinglong (Frontiers in Endocrinology, 2023)
Background and Aims Studies showed that elevated preoperative serum uric acid(SUA) levels are associated with recurrence of atrial fibrillation(AF) after catheter ablation. UA:creatinine ratio(UCR - UA normalised for renal function) has appeared as a new biomarker and is considered to reflect endogenous UA levels preferably because it eliminates the influence of renal function. This study aimed to investigate the correlation between UCR and recurrence of AF after catheter ablation. Methods and Results A total of 233 consecutive patients with symptomatic, drug-refractory AF underwent catheter ablation. All participants underwent history-taking, physical examination and blood biochemistry analysis at baseline. After a mean follow-up of 23.99±0.76 months, recurrence rates for each UCR quartile (from lowest quartile to highest) were 10.9%, 23.6%, 23.6%, and 41.8%, respectively (P = 0.005). Multivariate Cox regression analysis revealed that UCR was an independent predictor of AF recurrence (HR 1.217, 95%CI 1.008-1.468; P = 0.041). Subgroup analysis showed that UCR was associated with AF recurrence in paroxysmal atrial fibrillation (HR 1.426, 95% CI 1.092-1.8608; P = 0.009) and in male patients (HR 1.407, 95% CI 1.015-1.950; P = 0.04). A cut-off point of 4.475 for the UCR had sensitivity of 65.5% and specificity of 59.6% in predicting AF recurrence (P = 0.001). Conclusion Our results demonstrate that elevated preoperative UCR is associated with recurrence of AF after catheter ablation, and it indicate UCR maybe a predictive factor for the recurrence of AF.